1994
DOI: 10.1034/j.1399-3054.1994.900207.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and carbohydrate content during stolon to tuber transition in potatoes (Solanum tuberosum)

Abstract: 1994. Gene expression and carbohydrate content during stolon to tuber transition in potatoes (Solarium tuberosum) -Physiol. Plant. 90: 285-292.In using an efficient and synchronised in vitro tuberisation system the transition of axillary buds from stolons to tubers in Soianum tuberosum L. cv. Bintje was followed. After 5 or 6 days on tuber-inducing medium all axillarj' buds had formed tubers which increased in size until the experiment was ended at day 10. Concomitantiy with the visible appearance of tubers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 7 publications
3
45
0
2
Order By: Relevance
“…The expression profile in the cDNA-AFLP data gives a picture very comparable to the Northern data presented here and in other papers (Park et al, 1985;Visser et aL, 1994). Very high abundance of a particular transcript such as is the case with patatin can result in the occurrence of characteristic artefacts.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The expression profile in the cDNA-AFLP data gives a picture very comparable to the Northern data presented here and in other papers (Park et al, 1985;Visser et aL, 1994). Very high abundance of a particular transcript such as is the case with patatin can result in the occurrence of characteristic artefacts.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown the induction of patatin and AGPase in an in vitro tuberization system (Hendriks et aL, 1991;Visser et aL, 1994). We show here that the cDNA-AFLP method faithfully reproduces these results.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…and in S. brevidens Although the expression of the genes involved in starch synthesis is characteristic for potato tuber development [23], no corresponding cDNAs have been isolated from S. tuberosum by differential screening using S. brevidens as a negative partner. Therefore, we have decided to check the expression of these genes in developing shoots and tubers by Northern hybridization experiment.…”
Section: Expression Of the Starch Synthesis Genes In S Tuberosummentioning
confidence: 99%